UiTM student puppeteers made it to Malaysia book of records - Chan, Margaret Kit Yok (UiTM Sarawak, 2016)
The World Puppet Carnival organized by the Ministry of Culture and Tourism of Malaysia and the State of Sarawak was held in Kuching from 2nd to 8th November 2015. The best puppet production team for theatre, video and film consisted of not only Malaysian puppeteers but also those from all over the world such as Argentina, Japan, Finland, Australia, Singapore, the Philippines, Bulgaria, Turkey, Belgium, France, Algeria, USA, Kazakhstan, Guatemala, Liberia, Canada, Russia, Colombia, Belarus, and Poland.